Application of Industrial Treatment Plant Sludge and Heavy Metal Accumulation in Lettuce Plant (Lactuca sativa) - EKMEKYAPAR, F.; KAYKIOGLU, G. (Asian Journal of Chemistry, 2010)
Industrial treatment plant sludge application in agriculture was investigated. The effects of sludge at different loadings (0, 25, 50, 75 and 100 % sludge mixtures) and barnyard manure application as control set in lettuce plant, number of leaves, weight and heavy metal accumulation (Cd, Cr, Ni, Zn, Cu) in lettuce leaves were evaluated. The experiment was conducted using a completely randomized design with four replicates in Tekirdag province of Trakya region, Turkey in 2004. Sludge generated from organized industry region that is mostly composed of textile industries is applied to pots. The least significant difference (LSD) method is used to test the significance of sludge loadings. In general, 0-25-50-75-100 % of sludge treatments resulted in increase the number of leaves and weight in lettuce due to high inorganic nutrient (N and P) content of sludge loadings. In addition, heavy metal concentrations were measured in plant leaves and compared with the acceptable limits given for lettuce plant. The results indicated that application of sludge did not significantly increase nickel, cadmium and chromium contents of lettuce plant while zinc and copper content had significant (p < 0.05) effect. Although, copper content was between limits, zinc content was higher than the limit values. The results from pot experiments demonstrated that sludge used in the study can not be used as a partial substitute of chemical fertilizers. Accordingly, application doses of sludge below 25 % (20, 15, 10, 5 % sludge ratio) has been prepared and further experiments should be conducted to evaluate the heavy metal intake rates and accumulation in the plants.